Long-term efficacy, safety and durability of Juvéderm® XC - Ballin, Annelyse C (Dove Medical Press, 2013)
Over the last decade, there has been increasing interest in minimally invasive cosmetic treatments, especially for facial rejuvenation. Next to botulinum toxin injection, the injection of soft tissue fillers is the second most frequent minimally invasive procedure performed in the USA. Hyaluronic acid (HA) is the most commonly used dermal filler. One of patients’ main concerns about filler injections pertains to pain and discomfort. Topical anesthetics, nerve blocks, and/or the incorporation of lidocaine to the filler have been applied in order to reduce distress and pain. Despite nerve blocks being an effective form of anesthesia, they may distort the area to be treated, as well as lengthen and complicate the procedure. Studies have shown that the incorporation of lidocaine to HA fillers significantly reduces pain and discomfort. Yet, one of the dilemmas about the addition of lidocaine solution to HA fillers is the possible alteration of the physical characteristics of the product by negatively impacting the efficacy and/or duration of the filler. The concern is that the addition of lidocaine could dilute the product, creating less correction per mL, changing the product’s viscosity and consequently the “lifting” ability. Also, this dilution could reduce the product’s duration. There may be a difference between a physician adding an aqueous solution into a lidocaine-free version of HA and the pre-incorporated lidocaine version of HA. An aqueous solution might dilute the product, while the pre-incorporated powder lidocaine appears to avoid this problem. Juvéderm® XC is manufactured with powder lidocaine 0.3%; it is associated with significantly less injection pain than Juvéderm® and other lidocaine-free versions of HA. Studies have shown that lidocaine enhances treatment comfort and optimizes the injection experience while maintaining a similar safety and effectiveness profile. Regarding the longevity, further study is necessary to determine if there is any difference in durability.